Characterization of AbiR, a novel multicomponent abortive infection mechanism encoded by plasmid pKR223 of Lactococcus lactis subsp. lactis KR2 - Twomey, Denis P. (2000)
The native lactococcal plasmid pKR223 encodes two distinct phage resistance mechanisms, a restriction and modification (R/M) system designated LlaKR2I and an abortive infection mechanism (Abi) which affects prolate- headed-phage proliferation. The nucleotide sequence of a 16,174-bp segment of pKR223 encompassing both the R/M and Abi determinants has been determined, and sequence analysis has validated the novelty of the Abi system, which has now been designated AbiR. Analysis of deletion and insertion clones demonstrated that AbiR was encoded by two genetic loci, separated by the LlaKR2I R/M genes. Mechanistic studies on the AbiR phenotype indicated that it was heat sensitive and that it impeded phage DNA replication. These data indicated that AbiR is a novel multicomponent, heat-sensitive, 'early'- functioning Abi system and is the first lactococcal Abi system described which is encoded by two separated genetic loci.